PENERAPAN TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI RUMAH SAKIT UMUM DAERAH UNGARAN: THE IMPLEMENTATION OF SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) THERAPY ON BLOOD PRESSURE DECREASES IN HYPERTENSION PATIENTS AT UNGARAN REGIONAL GENERAL HOSPITAL - Rina Elsa Rizkiana; Dwi Mulianda (JURNAL KEPERAWATAN SISTHANA, 2021)
Hypertension is an increses of blood pressure which the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. SEFT therapy includes mind-body relaxation techniques that combine the body's energy system (energy medicine) and spiritual therapy with the tapping method at certain points on the body along the 12 energy pathways (energy meridians) of the body. The purpose of the case study was to describe the effect of SEFT therapy on the reduction of blood pressure in hypertension patients at Ungaran Regional General Hospital. The case study method used is a descriptive case study. The case study subjects were used as many as two people and had blood pressure above the normal limit. The data are obtained by observing and measured using a sphygmomanometer before and after therapy. The results of the case study show that the blood pressure of subject I decreases from 140/100 mmHg to 130/90 mmHg, while the blood pressure of subject II decreases from 150/110 mmHg to 140/100 mmHg. The conclusion of the case study is that the application of SEFT therapy is effective for reducing the blood pressure in patients with hypertension. For the development of nursing science and technology we suggest that to be able to apply SEFT therapy together with medical therapy in hospitals.